Development of upper garments with self-help features for children with down syndrome a case study - Oliveros, Katrina Gianina J.
This is a descriptive case study aimed to design and construct garment tops with self-help features of two selected children with Down syndrome. Specifically, this study aimed to determine the capabilities of selected children with Down syndrome in the wearing of tops identify garment self-help features that may aid selected children with Down syndrome design and construct a shirt for children with Down syndrome and wear test the proposed garments and evaluate effectiveness. The identification of clothing details could help children with Down syndrome because it would provide helpful information on local special clothing. The study was conducted by assessing the needs of two children with Down syndrome purposively selected from the Alternative Learning Resource School Philippines (ALRES). The data gathering involved three phases. In the first phase, observation of the children and interviews with the therapists were done. Using the data gathered in the first phase, proposed designs of garment tops were developed and constructed. The final phase involved the wear test and evaluation of effectiveness of the garments. For this study, the researcher concentrated on addressing these specific needs by using the design of the proposed garments to help them in their difficulties. For the buttons, the proposed garments were designed to be" button exercise shirts", wherein, the button sizes were progressive to train the hands of the children to quickly adapt to different sizes of objects in a single event. The buttons used had gripping features to help the children keep their grasp and minimize slippage. The buttons were in different colors and the colors of each button match its respective buttonho9le to provide visual cues for the children. One of the proposed garments also had visual cues for right and left to help the child distinguish one side from another. After the wear test, it had been observed that the gripping features of the buttons helped the children accomplish the task faster. The progressive button sizes gave the children an opportunity top try manipulating a variety of shape sizes and the observer and the teacher an idea of the cap0abilities of the children in terms of button manipulation. The color-matching feature of the garment was able to address the child's difficulty in matching the buttons to their respective buttonholes. The visual cues of left and right were still challenging for the child and would need further observations to validate effectiveness. It is recommended to consider construction details and more subjects in future studies.